A Critical Review of Nuova Grammatica Pratica Della Lingua Italiana - Mahzad Sheikholislami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this article we try to have a contextual and structural review about the first part of Nuova Grammatica Pratica Della Lingua Italiana written by Susanna Nocchi. This book was published in 2002 for the first time by Alma publications; and in 2011 was republished in a new and modified version. In current academic year (2017-2018), the first part of this book has been used for teaching Italian grammar to pre-university students of Italian literature in Faculty of Foreign Languages and Literatures of University of Tehran. The current article not only tries to express weaknesses and strengths of this grammar book but also attempts to highlight its cultural orientation.